Hvordan trøster du spedbarnet ditt? A field of tension between intuitive behavior, culture and knowledge - Landsem, Inger Pauline (Nordisk Tidsskrift for Helseforskning, 2022)
This essay address the phenomena comfort and caregivers may adapt their comporting actions to an infants soothability. Reflections about the importance of comfort and calming support of infants is done, and related to how caregivers’ capacity to comfort might be affected by intuitive behaviours, culture, and research and experiential knowledge. Comfort in this phase of life is interwoven in basic care, and the child needs frequent support to modulate inappropriate activity in an immature nervous system. A main focus is directed on the infant’s total dependence, but also the caregivers’ ability to understand the expressiveness and resources of the little person they interact with.